Dialogical Practices as Basis of the Self - Lyra, Maria; Bertau, Marie-Cecile (Studia Psychologica: Theoria et praxis, 2008)
The phenomenon of abbreviation in dialogue offers the opportunity to examine basic characteristics of dialogue as such. In this paper, two manifestations of this phenomenon are brought under special consideration: the historically constructed abbreviated dialogues in early life and abbreviation found in adult dialogues. We first examine the constructive role of preverbal dialogical practices in early life, focusing on dialogue as a system of communication that allows for the construction of new patterns of organization in the mother-infant communication system. Abbreviation occurs as a dialogical achievement in which we can identify the emergence of a dialogical self and the seeds of symbolic functioning. A microanalytic examination of abbreviated mother-infant dialogues suggests that the infant is differentiating his/her position in dialogue through the condensation of a relational history. This achievement has the characteristic of carrying both a relational and an individual dimension. The notion of abbreviation as pervasive in dialogical speech is to be found in Yakubinsky's seminal article On Dialogical Speech (1923), referring precisely to the kind of condensed relational history of self and other observed in infancy. Yakubinsky explores under what circumstances abbreviation does occur and gives six motives for this reduction. Most importantly, it is that partners' mutual understanding can rely on a well shared “mass of apperception” - dialogues can then proceed almost without language. Hence, basic dialogicity, as we assume axiomatically for human existence and self formation, manifests itself in different, more or less abbreviated dialogical practices. As a conclusion, it is assumed that dialogical self is the one that has an abbreviated relational history. The self is dialogical because it has internalized a selection of historically constructed dialogues that are abbreviated-condensed.